Learning Profiles of Slow Learner Students on Periodic Properties of Elements Using E-LAPD - Dian Novita; Hana Salsabila Virani; Teguh Bedjo Santoso; Rahmania Fitrah Sari; Findiyani Ernawati Asih (PLD UIN Sunan Kalijaga, 2026)
Slow learner students require adaptive chemistry learning support to understand abstract concepts. This research aims to explore the learning profiles and learning outcomes of slow learner students using Electronic Student Activity Sheets (E-LAPD) with individualized learning strategies on the topic of periodic properties of elements. Participants consisted of three slow learner students at Senior High School 10 Surabaya. This research employed a mixed-method approach using an embedded design. Qualitative data were analyzed using NVivo 11 software, while quantitative data were analyzed using N-gain scores to measure learning outcomes. The findings indicated a dominant visual learning tendency, although one student also demonstrated an auditory preference. The results also showed improved learning outcomes with a high average N-gain score. These findings highlight that E-LAPD can support inclusive chemistry learning by accommodating diverse learning needs and facilitating adaptive and inclusive learning for slow learner students. AbstrakSiswa slow learner memerlukan dukungan pembelajaran kimia yang adaptif untuk memahami konsep-konsep abstrak. Penelitian ini bertujuan untuk mengeksplorasi profil belajar dan hasil belajar siswa slow learner menggunakan Lembar Aktivitas Peserta Didik Elektronik (E-LAPD) dengan strategi pembelajaran individual pada materi sifat periodik unsur. Partisipan penelitian terdiri atas tiga siswa slow learner di SMA Negeri 10 Surabaya. Penelitian ini menggunakan pendekatan mixed methods dengan desain embedded. Data kualitatif dianalisis menggunakan perangkat lunak NVivo 11, sedangkan data kuantitatif dianalisis menggunakan skor N-gain untuk mengukur hasil belajar. Temuan menunjukkan adanya kecenderungan gaya belajar visual yang dominan, meskipun satu siswa juga menunjukkan preferensi auditori. Hasil penelitian juga menunjukkan peningkatan hasil belajar dengan rata-rata skor N-gain yang tinggi. Temuan ini menunjukkan bahwa E-LAPD dapat mendukung pembelajaran kimia inklusif dengan mengakomodasi kebutuhan belajar yang beragam serta memfasilitasi pembelajaran yang adaptif dan inklusif bagi siswa slow learner.